Endoscopic lung volume reduction coils for patients with severe emphysema—a single-centre retrospective analysis. (7th May 2021) - Mang, Sebastian; Huss, Niklas; Schäfers, Hans-Joachim; Wehrfritz, Holger; Massmann, Alexander; Lensch, Christian; Langer, Frank; Seiler, Frederik; Bals, Robert; Lepper, Philipp M
Abstract: : OBJECTIVES: Patients with chronic obstructive pulmonary disease and lung emphysema may benefit from surgical or endoscopic lung volume reduction (ELVR). Previously reported outcomes of nitinol coil-based ELVR techniques have been ambiguous. The analysis was done to analyse outcomes of ELVR with nitinol coils in patients with severe pulmonary emphysema. METHODS: From September 2013 to November 2014, our centre performed a total of 41 coil implantations on 29 patients with severe emphysema. Coils were bronchoscopically placed during general anaesthesia. Twelve out of 29 patients received staged contralateral treatments up to 112 days later to avoid bilateral pneumothorax. Lung function and 6-min walking distance were assessed 1 week prior, 1 week after as well as 6–12 months after the procedure. Patients were followed up to 48 months after ELVR and overall mortality was compared to a historic cohort. RESULTS: While coil-based ELVR led to significant short-term improvement of vital capacity (VC, +0.14 ± 0.39 l, P = 0.032) and hyperinflation (Δ residual volume/total lung capacity −2.32% ± 6.24%, P = 0.022), no significant changes were observed in 6-min walking distance or forced expiratory volume in 1 s. Benefits were short-lived, with only 15.4% and 14.3% of patients showing sustained improvements in forced expiratory volume in 1 s or residual volume after 6 months. Adverse events included haemoptysis (40%) and pneumothorax (3.4%), major complications occurred in 6.9% of cases. Overall survival without lung transplant was 63.8% after 48 months following ELVR, differing insignificantly from what BODE indices of patients would have predicted as median 4-year survival (57%) at the time of ELVR treatment. CONCLUSIONS: ELVR with coils can achieve small and short-lived benefits in lung function at the cost of major complications in a highly morbid cohort. Treatment failed to improve 4-year overall survival. ELVR coils are not worthwhile the risk for most patients with severe emphysema.